2018
DOI: 10.1186/s12936-018-2481-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three diagnostic methods (microscopy, RDT, and PCR) for the detection of malaria parasites in representative samples from Equatorial Guinea

Abstract: BackgroundMalaria in Equatorial Guinea remains a major public health problem. The country is a holo-endemic area with a year-round transmission pattern. In 2016, the prevalence of malaria was 12.09% and malaria caused 15% of deaths among children under 5 years. In the Continental Region, 95.2% of malaria infections were Plasmodium falciparum, 9.5% Plasmodium vivax, and eight cases mixed infection in 2011. The main strategy for malaria control is quick and accurate diagnosis followed by effective treatment. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
234
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(260 citation statements)
references
References 37 publications
18
234
2
6
Order By: Relevance
“…Therefore, our study corroborates the limitations of microscopy in the detection of P. vivax and P. knowlesi, that have been clearly demonstrated in large scale studies in S. E. Asia [13,14] Our study also suggests that P. knowlesi, which is thought to be predominantly a S. E. Asian parasite, is now also emerging in the Indian mainland.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, our study corroborates the limitations of microscopy in the detection of P. vivax and P. knowlesi, that have been clearly demonstrated in large scale studies in S. E. Asia [13,14] Our study also suggests that P. knowlesi, which is thought to be predominantly a S. E. Asian parasite, is now also emerging in the Indian mainland.…”
Section: Discussionsupporting
confidence: 88%
“…Asia [8][9][10][11] with a single report from the Andaman and Nicobar Islands of India [12]. In many malaria cases in endemic areas severe malaria symptoms such as AKI manifest, but malaria diagnosis by microscopy or RDT is made only in a proportion of these cases, and the rest remain as occult malaria infections [13][14][15][16]. An earlier study from our center, based on which this study has been built, had reported the presence of peripheral P. vivax infection in patients with AKI [17].…”
Section: Introductionmentioning
confidence: 99%
“…DNA-based malaria assays in general, and PCR in particular, are significantly more sensitive than microscopy and RDTs. Limit of detection (LOD) for PCR is typically 1-5 parasites/µL [13][14][15][16][17] compared to 50-500 parasites/µL for microscopy [13,14,18] and more than 100 parasites/µL for RDT's [14,19]. Depending on the assay, PCR can be used for accurate species identification, detection of mixed infections, and parasite density estimation [20].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1,724 blood samples were diagnosed by microscopy, SnM-PCR and RDT [21]. The Plasmodium sp.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were collected from a cross-sectional survey conducted in June-August 2013 in Bata as part of a project called "PREVAMAL". A total of 1,741 individuals (1,043 in urban settings and 698 in rural) were recruited [20,21]. Figure 1 shows the different locations where the samples were collected.…”
Section: Study Populationmentioning
confidence: 99%